I Am a Nigerian in Stem - Oyeleye, Foluke; Olaleye, Oluwadamilola (Nigeria, 2022)
This collection is an inspiring treasure trove of 15 Nigerians in the fields of Science, Technology, Engineering, and Mathematics. Many of them were pioneers - the first Nigerians in their fields or the first to attain certain achievements - but their excellence goes beyond being the first or the best...
Keywords: Biography; Famous People; Juvenile Non-Fiction